A Giant Frontal Meningioma with Psychiatric Symptoms in a Young Woman: A Case Report - Dinh, Hoai; Tran, Dang Thi; Tran, Thi Mai Dieu; Pham, Hai Duong; Nguyen, Vinh Lac; Nguyen, Thanh Minh (International Clinical Neuroscience Journal, 2021)
Background:Frontal meningioma is often asymptomatic but patients might experience psychiatric symptoms. Since symptoms are atypical in giant meningioma, to the best of our knowledge, we present a rare clinical scenario. Case Presentation: A 24-year old female patient with no medical history presented with two months of depressive symptoms, personality changes such as easy irritability, and feelings of frustration and mental depression, as well as forgetfulness and blurred vision. Brain magnetic resonance imaging (MRI) revealed a well-defined markedly enhancing lesion in the left frontal region measuring 65 x 70 x 70 mm with mass effects to the adjacent brain tissue and associated surrounding edema which was pressed to the frontal horn of the lateral ventricle. The patient underwent frontal unilateral craniotomy and excision of the tumor. After surgery, the quality of life was improved. Conclusion: Meningioma with psychiatric symptoms is quite rare. This clinical case helps clinicians avoid missing symptoms and use appropriate management strategies for patients with giant meningiomas.